2020
DOI: 10.3389/fvets.2020.584922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meperidine on Equine Blood Histamine, Tryptase, and Immunoglobulin-E Concentrations

Abstract: Objectives: To evaluate changes in immunological parameters following subcutaneous (SC) and intramuscular (IM) administration of meperidine in horses through quantitative analysis of plasma tryptase, histamine, and IgE levels.Methods: Six adult horses were enrolled in a prospective randomized crossover design. Horses were administered one treatment per day, with a seven day washout period: (a) meperidine 1 mg/kg IM, saline 6 mL SC; (b) saline 6 mL IM, meperidine 1 mg/kg SC; (c) saline 6 mL SC, saline 6 mL IM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Trenholme et al. ( Trenholme et al., 2020 ) showed that IM or subcutaneous administration of pethidine did not induce histamine release, whereas a clinical case report from Clutton ( Clutton, 1987 ) strongly suspected that histaminic effects led to hypotension and tachycardia in two horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trenholme et al. ( Trenholme et al., 2020 ) showed that IM or subcutaneous administration of pethidine did not induce histamine release, whereas a clinical case report from Clutton ( Clutton, 1987 ) strongly suspected that histaminic effects led to hypotension and tachycardia in two horses.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent equine study, specific focus was placed on blood parameter level changes associated with pethidine injection. Subcutaneous and intramuscular (IM) administration of pethidine did not induce a statistically significant increase in concentration of histamine, tryptase, or IgE compared to the baseline values ( Trenholme et al., 2020 ). However, in all horses, subcutaneous pethidine injection caused localized vasculitis and thrombosis with regional edema and hemorrhage ( Trenholme et al., 2020 ).…”
Section: Introductionmentioning
confidence: 90%